Efektivitas Penerapan Joyful Learning Menggunakan Kartu Tahfidz Terhadap Kemampuan Menghafal Al–Qur’an dan Happiness Siswa TK - Zulfiyanti, Novi; Aisyah, Siti; Surbakti, Amanah (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
One important aspect of early childhood education is the introduction to and memorization of the Qur'an, which plays a role in cognitive development and the formation of religious character. However, conventional and rigid learning approaches often cause children to feel bored and unmotivated to memorize. To overcome this, a fun approach is needed, such as joyful learning. This study aims to examine the effectiveness of the joyful learning approach using tahfidz cards in improving the Quran memorization ability and happiness of kindergarten students. This study used a quasi-experimental method with a non-randomized pretest-posttest control group design. The subjects consisted of 34 kindergarten students in Medan City, divided into two groups: experimental and control, each with 17 students. Data were collected through a Quran memorization test and a children's happiness scale, then analyzed using the paired sample t-test and independent t-test. The results indicate that the joyful learning approach significantly improves memorization ability (t = 11.830, p = 0.000) and student happiness (t = 7.062, p = 0.000). The average increase in memorization was 17.706 points and happiness was 9.353 points. This study emphasizes the importance of joyful learning in supporting children's potential and emotional well-being.